Molecular and Microbiological Insights on the Enrichment Procedures for the Isolation of Petroleum Degrading Bacteria and Fungi - Spini, Giulia; Spina, Federica; Poli, Anna; Blieux, Anne-Laure; Regnier, Tiffanie; Gramellini, Carla; Varese, Giovanna C.; Puglisi, Edoardo (Frontiers in Microbiology, 2018)
Autochthonous bioaugmentation, by exploiting the indigenous microorganisms of the contaminated environment to be treated, can represent a successful bioremediation strategy. In this perspective, we have assessed by molecular methods the evolution of bacterial and fungal communities during the selective enrichment on different pollutants of a soil strongly polluted by mixtures of aliphatic and polycyclic hydrocarbons. Three consecutive enrichments were carried out on soil samples from different soil depths (0–1, 1–2, 2–3 m), and analyzed at each step by means of high-throughput sequencing of bacterial and fungal amplicons biomarkers. At the end of the enrichments, bacterial and fungal contaminants degrading strains were isolated and identified in order to (i) compare the composition of enriched communities by culture-dependent and culture-independent molecular methods and to (ii) obtain a collection of hydrocarbon degrading microorganisms potentially exploitable for soil bioremediation. Molecular results highlighted that for both bacteria and fungi the pollutant had a partial shaping effect on the enriched communities, with paraffin creating distinct enriched bacterial community from oil, and polycyclic aromatic hydrocarbons generally overlapping; interestingly neither the soil depth or the enrichment step had significant effects on the composition of the final enriched communities. Molecular analyses well-agreed with culture-dependent analyses in terms of most abundant microbial genera. A total of 95 bacterial and 94 fungal strains were isolated after selective enrichment procedure on different pollutants. On the whole, isolated bacteria where manly ascribed to Pseudomonas genus followed by Sphingobacterium, Bacillus, Stenothrophomonas, Achromobacter, and Serratia. As for fungi, Fusarium was the most abundant genus followed by Trichoderma and Aspergillus. The species comprising more isolates, such as Pseudomonas putida, Achromobacter xylosoxidans and Ochromobactrum anthropi for bacteria, Fusarium oxysporum and Fusarium solani for fungi, were also the dominant OTUs assessed in Illumina.